دَوَر اَلمسجدَ فَي اَلتَنشئةَ اَلاجتماعية وَالوقايةَ مَن اَلانحراف دراسة مَيدانيةَ عَلى بَعضَ اَلمساجدَ اَلواقعةَ فَي مَدينةَ زَليتنَ لَيبيا - Khadija M. Alsari
This study aims to determine the role played by the Mosque in socialization and ensuring prevention against deviance and various employed to fulfil this role pursuant to this endeavour, it will address the following main question: what is the role that Mosque can render toward socialization and ensuring prevention against deviance? The present study carries pragmatic significance. It shows the formidable role of the Mosque as an educational and informative institution. As such, it keeps community protected against deviance and assures it lasting peace and stability. The present study also carries academic importance. It represents a scholastic advance on the area. As such, it enriches Arabic library on the subject. Further, it seeks to fill a major gap. For, existing study on the relative role of the Mosque in ensuing prevention against deviance are scanty. This gap will be filled. The researcher has used analytical- descriptive approach. Pursuant to this approach, it has provided fine discourse quantitatively and qualitatively, the questionnaire was the main tool for data collection. The present study has offered the following finding; Worship role of the Mosque ranks foremost in socialization and ensuring deviance prevention. It is graded as “very good”, guidance role of the Mosque is next in importance in socialization and ensuring deviance prevention. It is graded as “ largely good” , educational role of the Mosque is third in sequence of importance. it is graded as “ large only”, suggestive solutions on activating the role of Mosque toward deviance prevention are in general, substantial.